Pengaruh Kebasahan Tanah terhadap Perubahan Daya Serap Air Gambut Terbakar di Kecamatan Landasan Ulin Kalimantan Selatan - Syahbian Syahbian; Syaifuddin Syaifuddin; Abdul Haris (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
Peat swamp land in Indonesia is quite extensive, which is 10.8% of Indonesia's land area, the area of peatland in Indonesia is estimated at around 14.95 million hectares, the largest on the islands of Sumatra, Kalimantan and Papua and a small part in Sulawesi. The dry process is not good can be associated with bulk density. Irreversible dryness can occur in peat with low lindak density, while peat with high lindak density is relatively easy to reabsorb water. Peat soils store much higher carbon than mineral soils. Every gr of dry peat stores about 180-600 mg of carbon, while every gr of mineral soil contains only 5-80 mg of carbon. This research method uses a descriptive exploratory method whose variable approach is carried out through land surveys and is supported by the results of soil analysis in the laboratory. The results showed the value of water content and water absorption of peat soil in the protected forest of Banjarbaru peat soil based on different times and showed a decrease in the level and absorption of peat soil.